Strategi Dinas Perpustakaan dan Kearsipan Kota Tanjung Balai dalam Meningkatkan Minat Kunjung Pemustaka - Maisya, Aprilla; Sayekti, Retno; Fathurrahman, Muslih (ARZUSIN, 2024)
This research aims to find out the causes of the decline in visitor interest at the Tanjung Balai City Library and Archives Service, the strategies implemented by the Tanjung Balai City Library and Archives Service to encourage users' interest in coming to the library, find out what obstacles are faced by the City Library and Archives Service Tanjung Balai in arousing interest in visiting the library. This type of research is qualitative research with a field approach. The subjects of this research are librarians who work at the Tanjung Balai City Library and Archives Service and the community around the library. The data collection techniques used include observation, interviews and documentation. The data analysis technique used is based on descriptive analysis, namely data reduction, data presentation and drawing conclusions. From the results of research conducted by the author, it can be concluded that the cause of the decline in interest in visiting the Tanjung Balai City Library and Archives Service is the lack of incomplete facilities and infrastructure and a lack of public awareness about the importance of reading books to increase knowledge. Furthermore, the strategy used by librarians to increase interest in visiting visitors is to create various activities including mobile libraries and several literacy competitions, which are very helpful in attracting people's sympathy for reading.